Sports in Udmurt State Agrarian University (using the example of participation in various competitions from 1954 to 2024) - Rubtsova, Lyubov V.; Zhuikov, Roman A.; Vorotova, Maria S. (Физическое воспитание и студенческий спорт)
Udmurt State Agrarian University (UdGAU) is one of the modern specialized educational institutions in Russia. This university is an educational, scientific and sports center for training agricultural specialists. Since the establishment of the university, the Department of Physical Education has also been established, which employed few specialists invited from other cities of Russia. Enthusiastic teachers searched for talented student-athletes, and various sports events were held. In the 1960s, the first masters of sports appeared in cycling, cross-country skiing, freestyle wrestling, and athletics. The history of the department was recorded by senior lecturer V. S. Pashkova, and then by the chairmen of the Institute’s sports club. A great contribution to the work of the department was made by Professor N. A. Solovyov, who worked for more than 50 years at UdGAU. In 2023, Professor N. A. Solovyov turned 90 years old and an international scientific and practical conference “Modern Problems of Physical Education and Sports in the Higher Education” was organized in his honor, which was attended by more than 70 people. Solovyov has written more than 120 scientific papers. He described the history of sports in the Udmurt Republic until 2023. The purpose of the study is to analyze the history of sports in UdGAU for the period indicated in the title of the article. The research methods used: analysis of archival materials of the department and the University of UdGAU, historical essays by N. A. Solovyov and Internet sources. A literary reviewand other sources provided information about the team and personal performances of UdGAU athletes from 1954 to 2024. The sports traditions of the Department of Physical Education, the names of the masters of sports who trained at the university, and traditional sports are also presented.